ANALYSIS OF BIOMASS AND CARBON STOCK ON MANGROVE FOREST ECOSYTEM THE TELUK PULAI, VILLAGE OF PASIR LIMAU KAPAS, ROKAN HILIR RIAU PROVINCE - Muhammad Syarif; Irvina Nurrachmi; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 2016. Sampling was conducted on mangrove forest ecosystems in Teluk Pulai Pasir Limau Kapas Rokan Hilir in Riau Province. The purpose of the research is to analyze the content of carbon in mangrove forest ecosystems as well as to determine the ability to these ecosystems to store carbon per unit area of mangrove forest area in the village of Teluk Pulai. The method used in this study is a survey method, which observation and sampling on the field and do the samples analyzed in the laboratory. Based on the average yield of total biomass of mangrove highest at station 1 is 198.58 ton/ha while the lowest was at station 3 is 68.80 tons/ha. The average yield of total carbon stocks are highest in station 1 with a value of 300.31 tons/ha while the total carbon stock was lowest for the station 3 with a value of 222.74 tons/ha.Keyword: Teluk Pulai, Mangrove, Biomass, Carbon